A STUDY TO ASSESS THE PREVALENCE OF DEPRESSION AND ANXIETY AMONG ANTENATAL MOTHER WITH GESTATIONAL DIABETES MELLITUS IN SELECTED HOSPITAL IN CHENNAI - S. Pappy Yuvarani,; Dr. V. Hemavathy, (The Bioscan, 2025)
Introduction: Gestational diabetes mellitus (GDM) is defined as glucose intolerance with onset or first recognition during pregnancy. Aim of the study: The aim of the study to assess the Prevalence of depression and anxiety among antenatal mother with gestational diabetes mellitus in selected hospital in Chennai. Methodology: The present study adopted a cross-sectional study design. The study was conducted at Sree Balaji Medical College and Hospital in Chennai. The required sample size for the study was calculated as 160. Using a convenience sampling technique, the sample was selected from antenatal mothers diagnosed with Gestational Diabetes Mellitus (GDM) attending the antenatal outpatient department (OPD) at the selected hospital. Pregnant women without GDM and those with other complications were excluded from the study. Results: The study found that among the 160 antenatal mothers with GDM, 37.5% experienced normal levels of anxiety, 25% had borderline anxiety, 18.75% showed moderate anxiety, and 18.75% had severe anxiety. In terms of depression, 43.75% of participants had normal levels, 31.25% were borderline, and 12.5% each experienced moderate and severe depression. A strong positive correlation of 0.75 was observed between anxiety and depression, suggesting that higher anxiety levels were strongly associated with increased depression levels among the study participants. Conclusion: The study's findings reveal a considerable prevalence of anxiety and depression among antenatal mothers with GDM, with a significant correlation between these two conditions.